Leukemia With TCF3-ZNF384 Rearrangement as a Distinct Subtype of Disease With Distinct Treatments: Perspectives From A Case Report and Literature Review - Lin, Na; Yan, Xiaojing; Cai, Dali; Wang, Lei (Frontiers in Oncology, 2021)
ZNF384 rearrangements are found in 5-10% of B-cell acute lymphoblastic leukemia (B-ALL) and 48% of B cell/myeloid mixed phenotype acute leukemia (B/M MPAL). ZNF384-rearranged B-ALL is prone to lineage conversion after chemotherapy. TCF3 is the second most common rearrangement partner of ZNF384 in B-ALL (27.5%) and the most common partner in B/M MPAL (53.3%). TCF3-ZNF384 fusion is related to a poor steroid response and a high frequency of relapse. It is mostly reported in children and adolescents  but rarely seen in adults.Here, we report a rare case of adult common B-ALL with TCF3-ZNF384 fusion in which the patient relapsed after one cycle of consolidation chemotherapy. Relapsed leukemia cells from the bone marrow were cultured for 72 hours ex vivo, and a panel of 156 kinds of cytotoxic drugs, targeted therapy drugs, combination chemotherapy drugs, etc., was used for sensitivity screening. The literature on TCF3-ZNF384 fusion was reviewed, and reported cases with TCF3-ZNF384 fusion were summarized. Clinical characteristics were compared between B-ALL and MPAL with TCF3-ZNF384 fusion.The relapsed lymphoblasts showed moderate sensitivity to both acute myelocytic leukemia (AML) - and acute lymphoblastic leukemia (ALL)-directed combination chemotherapy schemes, as well as to multiple targeted therapeutic drugs. The hyper-CVAD (B) scheme showed synergistic effects with multiple targeted compounds and had the highest sensitivity. The patient chose the hyper-CVAD (B) scheme combined with sorafenib and achieved complete remission (CR), then consolidated with myeloid-directed homoharringtonine+cytarabine+daunorubicin (HAD) scheme and gained molecular CR. By reviewing the literature, we found that both the genomic landscapes and gene expression profiles of ZNF384-rearranged B-ALL and MPAL are similar and that both diseases have lineage plasticity. The gene expression profile in TCF3-ZNF384-positive patients shows enrichment of hematopoietic stem cell features. No significant differences in clinical characteristics were found between TCF3-ZNF384-positive ALL and MPAL.TCF3-ZNF384-positive leukemia may be a distinct subtype of leukemia regardless of immunophenotype. Considering the frequent lineage switches and sensitivity to both ALL- and AML-directed schemes, a uniform strategy directed at both lymphoid and myeloid lineages or at hematopoietic stem cells may be better for TCF3-ZNF384-positive leukemia. Small molecule targeted therapies may be promising treatment options and deserve further investigation.